Household Income, Consumption and Saving Behaviour: a Case Study of Two Rural Districts in Malaysia - Puteh Mahadi, Bahar (1988)
The incidence of poverty resulting from low income has been a persistent phenomenon in Malaysia, particularly in the rural areas. The problem is markedly prevalent among the smallholders' sub-sector involved in padi, rubber, coconut and fishing activities. As a result, there is a widespread belief that the rural households have very low propensity to save, and this limits the accumulation and availability of financial resources in this sector. This study i s conducted to examine the overall perspective related to income, consumption and saving of the rural households, with the main objective to determine with certainty the capacity to save prevalent among the households. Primary data were collected from specific areas of study and detailed analysis by regression was carried out using consumption models to determine the influence of such variables as farm sizes, dependents and sources of income on household consumption. From the results, inferences were drawn to explain household saving behaviour, while simultaneously comparing the findings with other studies in similar field, inside and outside the country. The result shows that there i s a strong capacity among the rural households to save their income. The analysed MPS lies in the region of 0.1 to 0.4 with the higher value prevalent among higher income families , especially those with bigger farm sizes. Low income families have to meet their basic consumption requirement for food, clothing and children education, causing the MPS to decline. Farm income constitutes the most important component of total household income and its size is significantly influenced by the size of farms and the types of cultivated crops. Households owning smaller farms are observed to rely heavily on non-farming activities to supplement their total household income. The findings of the study can be used as a guide for the formulation of rural development policy, particularly with respect to project financing and mobilisation of funds. With proper incentives and facilities, the target of reducing government involvement in agricultural development can be achieved, while at the same time, paving the way to encourage self-reliance among the smallholders sub-sector.